Development of Taste Masking Strategies of Few Selected Bitter Drugs - Karan, Gohil; P.K, Choudhury; Ranu, Sharma; Maya , Sharma (Asian Journal of Pharmaceutical Research and Development, 2025)
Taste is an important factor in the development of dosage form. Many orally administered drugs elicite bitter taste. Palatability is an extremely important factor in ensuring the likelihood that the recipient will take medicine. Previously the attitude of “Worse the taste of medicine, better the cure” was observed, but now-a-days several approaches of masking the bitter taste have been developed. It includes adding sugars, flavors, sweeteners, use of lipoproteins, numbing taste buds, coating drug, microencapsulation, multiple emulsion, viscosity modifier, vesicles and liposomes, prodrug and salt formation, inclusion and molecular complexes, solid dispersion, application of Ion Exchange Resins (IERs).Taste masking becomes a prerequisite for bitter drugs to improve the patient compliance especially in the pediatric and geriatric population. Formulating or dispersible, melt in mouth, buccal tablet and other formulations which comes in contact with taste buds taste is one of critical factor to be consider. Masking the bitter taste of drugs is a potential tool for the improvement of patient compliance which intern decides the commercial success of the product.